Can quantum mechanics fool the cosmic censor? - Matsas, George Emanuel Avraam [UNESP]; Richartz, M.; Saa, A.; Silva, A. R. R. da [UNESP]; Vanzella, D. A. T. (Amer Physical Soc, 2009)
We revisit the mechanism for violating the weak cosmic-censorship conjecture (WCCC) by overspinning a nearly-extreme charged black hole. The mechanism consists of an incoming massless neutral scalar particle, with low energy and large angular momentum, tunneling into the hole. We investigate the effect of the large angular momentum of the incoming particle on the background geometry and address recent claims that such a backreaction would invalidate the mechanism. We show that the large angular momentum of the incident particle does not constitute an obvious impediment to the success of the overspinning quantum mechanism, although the induced backreaction turns out to be essential to restoring the validity of the WCCC in the classical regime. These results seem to endorse the view that the cosmic censor may be oblivious to processes involving quantum effects.